Importance of Hepatic Portal Circulation for Insulin Action in Streptozotocin-Diabetic Rats Transplanted with Fetal Pancreases - Brown, Josiah (1979)
The importance of the hepatic portal circulation in the response to insulin was assessed in streptozotocin-diabetic rats transplanted with syngeneic fetal pancreases. Partial reversal of diabetes was accomplished by transplantation of two or three fetal pancreases beneath the capsule of the kidney; complete reversal followed shunting of the venous drainage from the transplants to the liver. Plasma glucose after streptozotocin of 509±31 mg/dl (mean±SEM) fell after transplantation to 395±23 and after the shunt to 143±5 mg/dl. Urine volume fell from 84±4 to 50±5 ml/d and then to normal (17±1 ml/d) after the shunt. Glucose excretion which was 8.1±0.3 g/d after streptozotocin fell after transplantation to 4.8±0.3 g/d and after the shunt completely disappeared from the urine. The disappearance rate of glucose injected into the circulation, which was 0.50±0.07%/min in untreated diabetes, increased to 1.39±0.38%/min after transplantation and to 2.52±0.31%/min after the shunt, not different from normal controls (2.79±0.25). Plasma immunoreactive insulin (IRI) was below normal (25-35 μU/ml) and unresponsive to glucose in untreated diabetic rats. After transplantation IRI levels ranged from 73-223 μU/ml and there was no rise after glucose injection. After the shunt both the basal IRI (36±5 μU/ml) and the peak response to glucose at 10 min (58±7 μU/ml) were the same as in normal controls (42±4 and 62±7 μU/ml, respectively). The fall in IRI after the shunt is explained by increased extraction of insulin passing into the liver and also diminished secretion. After removal of the transplants plasma glucose and urine values returned almost to pretransplant levels. Secretion of insulin by transplanted pancreases into the liver enhances the effectiveness probably by increased extraction and action and reveals the importance of the normal route for insulin delivery.